If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14p+29=35p+22
We move all terms to the left:
14p+29-(35p+22)=0
We get rid of parentheses
14p-35p-22+29=0
We add all the numbers together, and all the variables
-21p+7=0
We move all terms containing p to the left, all other terms to the right
-21p=-7
p=-7/-21
p=1/3
| 10z+1=10z+1 | | 2x+18+2x+18=6x-2 | | 4x+7/9-3x=1/4 | | 9+4n-1=3 | | 3(2z-7=5z+17 | | w-18=59 | | n^2+2=73 | | x/12=19 | | -5+w=10 | | y/11+4=-9 | | 12x+3=x+2 | | 5x-25+3x-5=180 | | (x^2-x-4)^(3/4)-2=6 | | 5(10)^(x+3)=5000 | | 24b^2/8b^2=352947 | | 2 = y4– 1 | | 15u-7u=16 | | x10=93,456.2 | | -1=0.5a+9 | | 5(10)^x+3=5000 | | (25/y+4)+(10/y+2)=(30/y+2)-(5/y^2+6y+8) | | 1/3(6x-9)=x-12 | | -q/2+25=q/3 | | −2(x+14)+1=5 | | d–(–17)=–14 | | 6x+4+5x-2x=58 | | x1/10=0.96 | | -c-8=c+2 | | -4n=-12.8 | | 14z+42=14z+21 | | (x+1.5)^2-81=0 | | 12-x/2+3=1 |